Splenectomy in patients with myeloproliferative neoplasms: efficacy, complications and impact on survival and transformation. Issue 1 (January 2014) - Santos, Fabio P. S.; Tam, Constantine S.; Kantarjian, Hagop; Cortes, Jorge; Thomas, Deborah; Pollock, Raphael; Verstovsek, Srdan
Abstract Splenectomy may be an effective therapeutic option for treating massive splenomegaly in patients with myeloproliferative neoplasms (MPNs). There are still limited data on its short- and long-term benefits and risks. Efficacy and short-term complications were analyzed in 94 patients with different MPNs who underwent splenectomy at M. D. Anderson Cancer Center. The long-term impact of splenectomy on overall survival (OS) and transformation free survival (TFS) was evaluated in 461 patients with myelofibrosis (MF) seen at M. D. Anderson, including 50 who underwent splenectomy during disease evolution. Splenectomy improved anemia and thrombocytopenia in 47% and 66% of patients, respectively. The most common complications were leukocytosis (76%), thrombocytosis (43%) and venous thromboembolism (16%). Post-operative mortality was 5%. Among patients with MF, splenectomy during disease evolution was associated with decreased OS (hazard ratio [HR] = 2.17, p < 0.0001) and TFS (HR = 2.17, p < 0.0001). This effect was independent of the Dynamic International Prognostic Scoring System. Splenectomy is a possible therapeutic option for patients with MF and other MPNs, and its greatest benefits are related to improvement in spleen pain and discomfort, anemia and thrombocytopenia. However, in patients with MF it appears to be associated with increased mortality.